Tourism Image, Experiential Value, Experiential Satisfaction dan dampaknya terhadap Revisit Intention - Endang Sulistya Rini; Yeni Absah; Beby Karina Fawzeea; Alfifto Alfifto (Mahesa Research Center, 2022)
The aim of this study was to determine the effect of tourism image, experiential value, experiential satisfaction, on revisit intention in Lake Toba. The population in this study is tourists who visit Lake Toba, North Sumatra with an unknown number, so that the sampling uses the formula from the Malhotra theory where the number of questions is multiplied by four to obtain a sample of 324 tourists. The results showed that tourism image had a positive and significant effect on experiential satisfaction, experiential value had a negative but significant effect, experiential satisfaction had a positive and significant effect on revisit intention, tourism image had a positive and significant effect on revisit intention through experiential satisfaction and experiential value had a negative effect but significant to revisit intention through experiential satisfaction.